Comparative Study of Emotional Intelligence among University Students Exemplified by a Ukrainian- Kazakhstan Sample - Hulias , Inesa; Sadirbekova , Dinara; Baimoldina , Laura; Kozhamkulova , Nazgul (Insight: the psychological dimensions of society, 2025)
The aim is а theoretical-empirical research of the expression of emotional intelligence among Ukrainian and Kazakh students in terms of cross-cultural components and gender differentiation. Methods. The Ukrainian sample consisted of 68 students in their second and third years at Yuriy Fedkovych Chernivtsi National University (Chernivtsi, Ukraine). The Kazakh sample also comprised 68 students studying from the first to fourth years at two universities: Al-Farabi Kazakh National University (Almaty, Kazakhstan) and Abai Kazakh National Pedagogical University (Almaty, Kazakhstan). The following methodologies were used: the “Emotional Intelligence Test” (Hall, 2007) and the “Methodology for Diagnosing Personal Motivation for Achieving Success and Avoiding Failure” (Elers, 2002). Results. Attention was drawn to the context of the socio-cultural space, particularly the social transformations covering Ukrainian and Kazakhstan society. No significant differences were found between the Ukrainian and Kazakhstan samples regarding cross-cultural characteristics. It was argued that the functionality of emotional intelligence may significantly decrease under the influence of stress factors, while the level of emotional intelligence will maintain relative constancy. Gender differences indicated significant superiorities for female subsamples: for the Ukrainian sample in the parameter of “empathy” and the Kazakh sample in the parameter of “emotional awareness”. These superiorities were explained as reflections of socio-cultural characteristics. It was noted that martial law actualizes sympathy and empathy as a desire to help among Ukrainian female students. At the same time, sustainable development allows Kazakhstan female students to focus on the discrete functions and properties of their feelings and emotions. Discussion and Conclusions. It was explained that the psychological correlations of “emotion management” and “self-motivation” with the dimensions of motivation confirm that the interpersonal components of emotional intelligence are reflected in the control of one’s emotions and feelings, which helps students act effectively – either achieving success or avoiding failure. The results obtained are advisable to implement in the educational process of universities.